Athmospheric Hydrocracking of Jatropha Oil Using Woodchar Catalyst - Hendriyana, Hendriyana; Nurdini, Lulu; Khotimah, Rizqi Ajeng Khusnul; Sukandi, Nur Refianti; Ainun, Tika Dwi; Nurjanah, Evi Ojo; Yunengsih, Yuyun; Khoerunnisa, Fadilah (Universitas Negeri Semarang, 2020)
Jatropha oil which is non-edible oil were hydro-crack at atmospheric pressure using an activated wood char catalyst in a fixed bed reactor. The hydro-cracking process was carried out at three temperature variations of 400, 450 and 500oC, and three variations of the oil feed injection rate of 2/2, 2/5 and 2 mL/10 minutes. The catalysts were characterized using SEM and BET. The composition of the liquid product obtained from the hydro-cracking process was analyzed using GC-MS. The effects of operating temperature and oil feed injection rate on oil recovery and conversion have been discussed. The results showed that the feed injection temperature and rate had an effect on the yield and conversion. The highest yield of 59.8% oil liquid products was achieved at a temperature of 450oC with injection rate of 2 mL/10 min. The composition of the oil-liquid product was dominated by heptanal at 32.9% -mass. Alkanes group contain C5 to C20 and alkene compounds consist of C8 until C18.